Distance of tumor to skin as a predictive marker for axillary lymph node metastasis in cases of breast carcinoma - A retrospective study - Sandeep S Ojha; Rubal A Jain; Ramrao G Nilkanthe; Farah J Meenai; Sharma Abhishek; Haritwal K Amit (Indian Journal of Medical and Paediatric Oncology)
Background: Breast cancer is arising as the most common cancer among women. Axillary lymph node status is considered as one of the most important predictors of survival in breast cancer and a very important component to the staging system. The tumors under the skin have abundant access to the dermal lymphatic and have an increased chance of metastasizing to draining lymph nodes. Aim of the Study: To evaluate whether distance of tumor to skin can be considered as a predictor for lymph node metastasis. Materials and Methods: This was a retrospective study on all operated cases of infiltrating mammary carcinoma from January 2013 to December 2016. Both lumpectomy and mastectomy specimens with invasive carcinoma component were included in the study. The distance of the tumor was measured from the base of the epidermis of the skin to the anterior margin of the tumor on gross examination or microscopically the closest invasive carcinoma component. The distance was measured, tabulated, and correlated with the nodal status on axillary node dissection. Also, compared are the other parameters such as size, site, and grade of the tumor. Results: Out of 200 patients enrolled, positive nodes were seen in 67.5% (135) of cases, of which tumor with distance from skin <0.3 cm show maximum nodal positivity (64.4%) and maximum cases with N2 and N3 disease (48.8%). Most important and significant finding was that 100% cases with tumor size corresponding in T2 size with skin invasion either grossly or microscopically and T3 size tumor with microscopically involving epidermis was positive for metastatic deposits in axillary nodes and 10/11 cases (90%) in T4 stage were positive. Conclusion: The distance of tumor from skin is an important predictor for Axillary lymph nodal metastasis in invasive breast cancers. Closer the tumor, the incidence of axillary nodal metastasis increases. Hence, distance of tumor from skin should be considered while evaluating a breast cancer patient.